Reconsidering Humanist Chaplaincy for a Plural Society: The Implications for Higher Professional Education. (25th February 2021) - Jacobs, Gaby; Damen, Annelieke; Suransky, Caroline; Kate, Laurens
Abstract : Recent developments in Dutch society and its healthcare system pose new challenges to humanist chaplaincy. Thus far, chaplaincy has been predominantly rooted in institutionalized religion, but it now has to serve a diversity of people who are increasingly secularized with personal ways of worldviewing. Moreover, chaplaincy is increasingly becoming a profession like many others, reducing the focus on its worldviewing competencies. The main question this article addresses is what this implies for the education of chaplains, more specifically for humanist chaplains who are educated on a Master's level course at the University of Humanistic Studies. Using the concepts of interprofessional learning communities (Stoll & Seashore Louis, 2007) and dialogical professionalism (Jacobs, 2010), two visions are put forward for developing the education of humanist chaplains that might also be relevant for other chaplaincy educational programs.